The Effect of Shame on Motor Learning and the Frequency of Self-Controlled Feedback - Jared M.Porter (IPHO-Journal of Advance Research in Games and Sports, 2024)
Making learners aware of their mistakes is a frequent strategy used by practitioners; the common assumption is that doing this will ultimately lead to improvements in motor behavior. However, making someone aware of their errors, especially in front of their peers, can cause the person to feel embarrassed or ashamed. The purpose of this study was to investigate the impact of induced shame on the performance and learning of a novel motor skill and the frequency of requested augmented feedback. Participants(N=80) practiced a manual tracking task on a rotary pursuit tracker. Participants were quasi-randomly assigned to one of the six experimental conditions (i.e., shame SC, shame shame-yoked, neutral shame-yoked, neutral SC, neutral neutral-yoked, and shameneutral-yoked). Participants assigned to the shame conditions were told during practice that their performance was below average, whereas participants in the neutral conditions were told that their performance was average. The results of the study indicatedthat shame did not have a meaningful effect on motor performance or learning. It was also concluded that the frequency of requested feedback was not significantly different between the two self-control groups (i.e.,shame-SC and neutral-SC).